Can Economics Explain Where All-Inclusive Deals are Offered? - Christian Bladh; Håkan J. Holm (Lund University, School of Economics and Management, Department of Economics, 2012)
This paper investigates why all-inclusive travel packages are offered at some hotels but not at others. By using the theory of transaction cost, it is argued that all-inclusive contracts mitigate a hold-up problem and that the severity of this problem varies with regards to the hotel's distance to the resort center. This hypothesis is tested empirically against data from 3798 hotel offers and is strongly supported. Additionally, some country-specific mechanisms related to the general price level and the degree of corruption are analyzed. Countries with all inclusive offers are characterized by a low price level and high corruption.
Keywords: D23; D86; L14; L83; 330; All-inclusive; contracts; hold-up; transaction cost; tourism